Re- imaging visual information complexity : a creative approach to information entropy, perception, identification and understanding - Andruszkiewicz, Jan L. (Curtin University, 2012)
The author considers the material nature and aesthetic role of information complexity in creative production. Outlining the context of computer based artworks within the visual/fine arts and the relationship of dematerialised media to digital code, computer science techniques are redefined as both artwork, and method of creative investigation. A discussion of several of the author’s artworks illustrates these themes.